Activated protein C promotes breast cancer cell migration through interactions with EPCR and PAR-1 - Beaulieu, Lea M. (2006)
Activated protein C (APC) is a serine protease that regulates thrombin (IIa) production through inactivation of blood coagulation factors Va and VIIIa. APC also has non-hemostatic functions related to inflammation, proliferation, and apoptosis through various mechanisms. Using two breast cancer cell lines, MDA-MB-231 and MDA-MB-435, we investigated the role of APC in cell chemotaxis and invasion. Treatment of cells with increasing APC concentrations (1–50 μg/ml) increased invasion and chemotaxis in a concentration-dependent manner. Only the active form of APC increased invasion and chemotaxis of the MDA-MB-231 cells when compared to 3 inactive APC derivatives. Using a modified “checkerboard” analysis, APC was shown to only affect migration when plated with the cells; therefore, APC is not a chemoattractant. Blocking antibodies to endothelial protein C receptor (EPCR) and protease-activated receptor-1 (PAR-1) attenuated the effects of APC on chemotaxis in the MDA-MB-231 cells. Finally, treatment of the MDA-MB-231 cells with the proliferation inhibitor, Na butyrate, showed that APC did not increase migration by increasing cell number. Therefore, APC increases invasion and chemotaxis of cells by binding to the cell surface and activating specific signaling pathways through EPCR and PAR-1.